Mediating cultural memory in Britain and Ireland from the 1688 revolution to the 1745 Jacobite rising - Davis, Leith 1960- (Cambridge University Press, 2022)
Of Documents and Declarations: Mediating the 1688 Revolution -- Remembering to Forget: Ireland, The War of the Two Kings and Cultural Amnesia -- National Correspondences: Print, Letters and the Company of Scotland's Darien Expedition -- Writing the 1715 Jacobite Rising: Periodical Networks and the Inscription of News -- Reading the 1745 Jacobite Rising: "Transitory News-papers," "Fleeting Pamphlets" and Knots of Cultural Memory -- Conclusion: "Living On" After 1745: From Cultural Memory to the Memory of Culture
Includes bibliographical references and index
Keywords: Collective memory / Great Britain / History / 18th century; National characteristics, British; Nationalism / Great Britain / History / 18th century; English prose literature / 18th century / History and criticism; Collective memory in literature; Politics and literature / Great Britain / History / 18th century; Printing / Political aspects / Great Britain / History / 18th century; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh